A Systematic Literature Review of the Current State of Knowledge Related to Interventions for Bereaved Parents. (December 2019) - Dias, Nancy; Hendricks-Ferguson, Verna L.; Wei, Holly; Boring, Elizabeth; Sewell, Kerry; Haase, Joan E.
Aims: The purpose of this systematic literature review is to describe the interventions for bereaved parents, evaluate intervention effectiveness through study methodology rigor, replicability, and theoretical foundations. Methods: We searched MEDLINE via PubMed (1966-2018), CINAHL (1937-present), PsycINFO (1887-present), and Embase (1947-present) using various search words and MeSH terms related to the study purpose. A blinded screening of title/abstract was performed, with conflicting inclusion decisions resolved through group discussions. Matrices for remaining articles were created and discussed among the team. The levels of evidence of the 9 records were rated from very low to high based on the Grading of Recommendations Assessment, Development, and Evaluation guidelines. Results: Our initial pool included 1025 articles. After the screening of titles/abstracts, 63 articles were retained for full-text reviews. Evaluated based on the inclusion/exclusion criteria, 9 records met the review criteria. Of the 9 records, 1 was graded as very low, 3 low, and 5 low to moderate. The interventions for bereaved parents varied from using single-model interventions such as expressive arts therapy and telephone support to multimodal interventions that combined resources (ie, peer support, resource packets, and health-care support). Only 1 study explicitly illustrated how its bereavement intervention was designed based on the proposed theoretical model. Conclusions: This review highlights the need for individualized, well-tested, and effective bereavement care interventions to support bereaved parents. In summary, the state of the science on interventions for bereaved parents is poor and much work needs to be done to effectively address the needs of bereaved parents, including both their physical and emotional health needs.